A zinc chloride-doped adhesive facilitates sealing at the dentin interface: A confocal laser microscopy study. (October 2017) - Toledano, Manuel; Osorio, Raquel; Osorio, Estrella; Cabello, Inmaculada; Toledano-Osorio, Manuel; Aguilera, Fátima S.
Abstract: The aim of this study was to ascertain the effect of Zn-doping of dental adhesives and mechanical load cycling on the micromorphology of the resin-dentin interdiffusion zone (of sound and caries affected dentin). The investigation considered two different Zn-doped adhesive approaches and evaluated the interface using a doubled dye fluorescent technique and a calcium chelator fluorophore under a confocal laser scanning microscopy. Sound and carious dentin-resin interfaces of unloaded specimens were deficiently resin-hybridized, in general. These samples showed a rhodamine B-labeled hybrid layer and adhesive layer completely affected by fluorescein penetration (nanoleakage) through the porous resin-dentin interface. It was thicker after phosphoric acid-etching and more extended in carious dentin. Zn-doping promoted an improved sealing of the resin-dentin interface, a decrease of the hybrid layer porosity, and an increment of dentin mineralization. Load cycling augmented the sealing of the Zn-doped resin-dentin interfaces, as porosity and nanoleakage diminished, and even disappeared in caries-affected dentin substrata conditioned with EDTA. Sound and carious dentin specimens analyzed with the xylenol orange technique produced a clearly outlined fluorescence when resins were Zn-doped, due to a consistent Ca-mineral deposition within the bonding interface and inside the dentinal tubules. It was more evident when load cycling was applied on specimens treated with self-etching adhesives that were Zn-doped. Micropermeability at the resin-dentin interface diminished after combining EDTA pretreatment, ZnCl2 -doping and mechanical loading stimuli on restorations. It is clearly preferable to include the zinc compounds into the bonding constituents of the self-etching adhesives, instead of into the primer ingredients. The promoted new mineral segments contributed to reduce or avoid both porosity and nanoleakage from the load cycled Zn-doped resin dentin interfaces. EDTA+SB-ZnCl2 or SEB·Bd-Zn doping are preferred to treat caries-affected dentin surfaces. ZnO-doping encouraged for etch-and-rinse adhesives. Graphical abstract: Highlights: Load cycling improved sealing of the dentin-interface after using Zn-doped adhesives. Load cycling of Zn-doped resin/EDTA-etch interfaces, avoided micropermeability. Zn-doping the bonding resin of self-etching adhesives produced dentin remineralization.